ACQUAINTANCE WITH SCIENTIFIC LITERATURE AND THEIR ANALYSIS WITHIN THE TOPIC OF DIGITAL AUDIO SIGNALS AND SOUND FREQUENCY CORRECTION - Muhamadiyev Abdivali Shukurovich; Isvandiyarova Madina Beknazarovna (Galaxy International Interdisciplinary Research Journal, 2024)
Importance and application of digital audio signal analysis. The essence of digital television, the operation of sound signal synthesis to correct the psychophysiological state of a person, the results achieved by digital signal processing. Analysis of an automatic signal correction system to improve the sound quality of loudspeakers and rooms. Aspects of predictive modeling in acoustic design. Learning the basics of digital signal processing in telecommunication systems. Information systems based on biometric identification of users. Cluster information speech units models. Consider changing the timeline. Music signals, Digital signal processing filtering algorithm Sound equalization using Matlab.